Factitious prey and artificial diets for predatory lady beetles: current situation, obstacles, and approaches for improvement: a review. Issue 5 (4th May 2017) - Sun, Yuan-Xing; Hao, Ya-Nan; Riddick, Eric W.; Liu, Tong-Xian
ABSTRACT: Predatory lady beetles (Coleoptera: Coccinellidae) are important natural enemies of many pests in crop ecosystems throughout the world. Although several species are currently mass-reared and sold by biocontrol companies, there is an urgent need to reduce rearing costs. Cost-effective mass rearing of lady beetles involves the use of factitious prey/foods or artificial diets in lieu of natural prey. This review summarises the literature on the various kinds of factitious prey/foods and artificial diets as well as the feeding efficiency of predatory lady beetles. Factitious prey/foods generally satisfy the nutritional requirements for development of lady beetles, and lepidopteran immatures are the most widely used species. However, artificial diets, based on vertebrate protein and devoid of arthropod constituents, often yield disappointing results. We also highlight several successful examples and novel approaches for improving feeding efficiency. Moreover, available approaches and perspectives for speeding up the development and screening of cost-effective diets for mass rearing are stated in this review.